Reconstruction of sea-surface temperatures in the Canary Islands during Marine Isotope Stage 11. Issue 1 (March 2020) - Clauzel, Thibault; Maréchal, Chloé; Fourel, François; Barral, Abel; Amiot, Romain; Betancort, Juan-Francisco; Lomoschitz, Alejandro; Meco, Joaquín; Lécuyer, Christophe
Abstract: The study of paleoclimates enables us to improve and better constrain climate models in order to forecast future climate variations. Marine Isotope Stage 11 (MIS11), which began around 425, 000 yr BP and lasted about 65, 000 yr, is a warm isotope stage of paramount importance, because the astronomical configuration was similar to the one characterizing the Holocene. Therefore, this warm isotope stage is the most appropriate analog to present-day climate known to date. This study aims to provide new data on sea-surface temperatures (SSTs) inferred from the carbon and oxygen isotope compositions of skeletal carbonates of marine invertebrates preserved in two marine deposits of the Canary Islands located at Piedra Alta, Lanzarote, and Arucas, Gran Canaria. According to published isotopic fractionation equations the marine deposit from Arucas recorded SSTs of 15.9 ± 2.2°C on average, while the tsunamite from Piedra Alta recorded SSTs of 21.2 ± 1.9°C on average. Absolute dating, mollusc assemblages, and calculated marine temperatures suggest that the Arucas marine deposit corresponds to the beginning of MIS11, while the Piedra Alta tsunamite was formed during MIS11c. These results show that low latitudes also experienced sizable SST changes during interglacial stages.